(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
. The release of metallic silver on the surface of polymers upon interaction with melts of silver and ammonium nitrate has been studied.